2004
DOI: 10.1042/bj20031753
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of integrin activation by the membrane-distal sequence of the integrin alphaIIb cytoplasmic tail

Abstract: Integrin cytoplasmic tails regulate integrin activation including an increase in integrin affinity for ligands. Although there is ample evidence that the membrane-proximal regions of the alpha and beta tails interact with each other to maintain integrins in a low-affinity state, little is known about the role of the membrane-distal region of the alpha tail in regulation of integrin activation. We report a critical sequence for regulation of integrin activation in the membrane-distal region of the alphaIIb tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The latter results are consistent with NMR studies that showed minimal effects of the PP mutations on the membrane proximal clasp [30]. However, other mutational studies [41], as well as independent approaches, do suggest a role of the C‐terminus of α IIb CT in α IIb β 3 activation [30,42]. Clearly, further investigation is needed.…”
Section: Changes In the Cytoplasmic Tail (Ct) Domainsupporting
confidence: 82%
“…The latter results are consistent with NMR studies that showed minimal effects of the PP mutations on the membrane proximal clasp [30]. However, other mutational studies [41], as well as independent approaches, do suggest a role of the C‐terminus of α IIb CT in α IIb β 3 activation [30,42]. Clearly, further investigation is needed.…”
Section: Changes In the Cytoplasmic Tail (Ct) Domainsupporting
confidence: 82%
“…Monoclonal Antibodies and Plasmids-PAC1, a monoclonal antibody specifically recognizing the active conformation of ␣IIb␤3, was a generous gift from Dr. S. J. Shattil (University of California, San Diego). 4 B10 is a non-function-blocking anti-␣IIb␤3 complex-specific monoclonal antibody produced in our laboratory (15,25). AP3, a non-function-blocking anti-␤3 monoclonal antibody, was obtained from GTI, Brookfield, WI.…”
Section: Methodsmentioning
confidence: 99%
“…A lipid-modified peptide containing the membrane-distal sequence (RPPLEED) inhibits agonist-induced ␣IIb␤3 activation (13). Mutation of the ␣IIb RPP distal sequence activates ␣IIb␤3 in a metabolic energy-dependent manner (14,15). These findings suggest that the membrane-distal region of the ␣IIb tail suppresses energy-dependent ␣IIb␤3 activation, although the mechanism responsible for activation of the ␣IIb␤3 mutants remains unclear.…”
mentioning
confidence: 99%
“…However, the molecular mechanisms of integrin αvβ3 affinity regulation have been hampered by the lack of a suitable model in cultured cells convenient for adhesion assay. It has been reported that the binding of αvβ3 to VN is regulated [27,28] ; however, the measurement of the alternation of the adhesion affinity of the αvβ3 expressing cells to VN has proven to be difficult.…”
Section: Introductionmentioning
confidence: 99%